2020
DOI: 10.1136/bjsports-2020-103316
|View full text |Cite
|
Sign up to set email alerts
|

Differences in sport-related concussion for female and male athletes in comparable collegiate sports: a study from the NCAA-DoD Concussion Assessment, Research and Education (CARE) Consortium

Abstract: ObjectivesTo examine sex differences in sport-related concussion (SRC) across comparable sports.MethodsProspective cohort of collegiate athletes enrolled between 2014 and 2017 in the Concussion Assessment, Research and Education Consortium study.ResultsAmong 1071 concussions (females=615; 57.4%), there was no difference in recovery (median days to full return to play) (females=13.5 (IQR 9.0, 23.1) vs males=11.8 (IQR 8.1, 19.0), p=0.96). In subgroup analyses, female recovery was longer in contact (females=12.7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 35 publications
2
29
0
Order By: Relevance
“…18,54 However, a more recent study found that women displayed no difference in recovery time compared with men playing comparable collegiate sports. 39 Nonvarsity cadets have A multivariable model examining the association between symptom status upon the initiation of an RTA protocol and RTA protocol duration while controlling for sex, varsity status, academic break, time from injury to RTA protocol initiation, concussion history, and site. also displayed longer RTA timelines when compared with varsity athletes.…”
Section: Symptom Endorsement and Reportingmentioning
confidence: 99%
“…18,54 However, a more recent study found that women displayed no difference in recovery time compared with men playing comparable collegiate sports. 39 Nonvarsity cadets have A multivariable model examining the association between symptom status upon the initiation of an RTA protocol and RTA protocol duration while controlling for sex, varsity status, academic break, time from injury to RTA protocol initiation, concussion history, and site. also displayed longer RTA timelines when compared with varsity athletes.…”
Section: Symptom Endorsement and Reportingmentioning
confidence: 99%
“…However, this may have inadvertently resulted in the exclusion of relevant studies. Since completion of the review, other relevant studies have been published but were not able to be considered within this review such as the Concussion Assessment, Research, and Education Consortium research ( 63 ). However, the key differences in methods used between these two fields of study are important to highlight to guide future research and to ensure optimal health care pathways are developed to support patients most effectively.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent prospective study found no overall difference in concussion recovery between male and female Division I athletes, while female Division II/III athletes had longer recovery. This suggests that modifiable extrinsic factors such as access to an athletic trainer or sports medicine specialist may also influence concussion outcomes [ 19 ••]. Injury prevention remains the greatest challenge in concussion management.…”
Section: Tailoring Prevention To High-risk Areasmentioning
confidence: 99%